2021
DOI: 10.3390/microorganisms9102176
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Polyethyleneimine (PEI) on Flat Surfaces and Nanoparticles Affects Its Ability to Disrupt Bacterial Membranes

Abstract: Interactions between a widely used polycationic polymer, polyethyleneimine (PEI), and a Gram-negative bacteria, E. coli, are investigated using atomic force microscopy (AFM) quantitative imaging. The effect of PEI, a known membrane permeabilizer, is characterized by probing both the structure and elasticity of the bacterial cell envelope. At low concentrations, PEI induced nanoscale membrane perturbations all over the bacterial surface. Despite these structural changes, no change in cellular mechanics (Young’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Thus, PEI was used to form a layer with higher positive charge. PEI due to the presence of many amino groups, including primary, secondary, and tertiary ones along its chain can present a high positive charge density 41 . Performing PEI led to charge reversal and changed the zeta potential to + 22 mV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PEI was used to form a layer with higher positive charge. PEI due to the presence of many amino groups, including primary, secondary, and tertiary ones along its chain can present a high positive charge density 41 . Performing PEI led to charge reversal and changed the zeta potential to + 22 mV.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some cationic polymers, including PDA and PEI, also have antibacterial activity and can destabilize the bacterial membrane. Their activity heavily depends on their structure, such as their molecular weight, type of functional groups, and form (linear or branched) 41 , 43 , 44 . Moreover, the combination of those cationic polymers with other antibacterial agents has led to the synergistic improvements in activity 45 .…”
Section: Resultsmentioning
confidence: 99%
“…It has recently gained significance as an adhesive antimicrobial coating material that binds to various inorganic and organic materials and can be formulated into drug delivery systems [ 43 ]. Furthermore, polyethylene imine (PEI), a cationic polymer with the ability to disrupt bacterial cell walls and membranes through pore formation, was crosslinked into the gelatin-PDA matrix in this study to confer antimicrobial activity to the fibers [ 41 , 44 , 45 , 46 ]. Due to its excellent gene encapsulation efficiency and its intrinsic endosomolytic activity, PEI is widely used for gene delivery purposes [ 47 ].…”
Section: Introductionmentioning
confidence: 99%